Human Risk in Work Situation: Theoretical Framework (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
To improve the contribution of human risk management in different work activities and thus to the general reliability of safety systems, this research proposes a theoretical framework for human risk management in work situations, through a detailed analysis design elements of human factors in the genesis of work accidents.